2022
DOI: 10.3389/fimmu.2022.838040
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Immunosuppression: The Multifaceted Functions of Tumor-Promoting Myeloid Cells in Breast Cancers

Abstract: Breast cancers are commonly associated with an immunosuppressive microenvironment responsible for tumor escape from anti-cancer immunity. Cells of the myeloid lineage account for a major part of this tumor-promoting landscape. These myeloid cells are composed of heterogeneous subsets at different stages of differentiation and have traditionally been described by their cardinal ability to suppress innate and adaptive anticancer immunity. However, evidence has accumulated that, beyond their immunosuppressive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 134 publications
(197 reference statements)
0
3
0
Order By: Relevance
“…"HER2-enriched" breast cancers are characterized by an amplification of HER2, and basal-like breast cancers correspond roughly to triple-negative breast cancers, which are HR − /HER2 − [8][9][10][11]. Further characterization of their tumor microenvironment (TME) reveals that these subtypes also differ in the composition of non-malignant elements, which may significantly impact responses to immunotherapies [12]. As such, TNBC patients, whose tumors are considered to be more immunogenic, are more responsive to an immune checkpoint blockade (ICB), such as immune inhibitory receptor PD1 inhibition [13,14].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…"HER2-enriched" breast cancers are characterized by an amplification of HER2, and basal-like breast cancers correspond roughly to triple-negative breast cancers, which are HR − /HER2 − [8][9][10][11]. Further characterization of their tumor microenvironment (TME) reveals that these subtypes also differ in the composition of non-malignant elements, which may significantly impact responses to immunotherapies [12]. As such, TNBC patients, whose tumors are considered to be more immunogenic, are more responsive to an immune checkpoint blockade (ICB), such as immune inhibitory receptor PD1 inhibition [13,14].…”
Section: Figurementioning
confidence: 99%
“…Myeloid cells encompass highly heterogeneous subpopulations, play a variety of roles in BC, and are considered the main drivers of tumor progression [12,[102][103][104]. Recent studies have reported that estrogen signaling contributes to the dysregulation of myelopoiesis observed in cancers [100].…”
Section: Er Signaling In the Immune Cells Of The Myeloid Lineagementioning
confidence: 99%
“…In BC, MDSC accumulation in the TME and peripheral circulation is notable, driven by the modulation of immunosuppressive mechanisms, predominantly through T-cell activation inhibition ( 17 ), along with the secretion of multiple cytokines and non-immunosuppressive pathways ( 18 ). This collective action promotes tumor growth by enabling tumor angiogenesis, enhancing invasion and metastasis, and modifying the TME to favor tumor progression ( 19 ).…”
Section: Introductionmentioning
confidence: 99%